SH.SEYITOV SHÍǴARMALARÍNDA SÚWRETLEW USÍLÍ – PARALLELIZMLER HAQQÍNDA - Sadenova, G.P. (ILIM hám JÁMIYET, 2024)
In the article, phonetic, lexical and syntactic elements are described in parallel, their features and the skill of using them in the artistic text are studied on the example of the prose works of the famous Karakalpak writer Shaudirbay Seyitov.